LANGUAGE TRENDS ACROSS SOCIAL MEDIA - Umaroh, Liya (Journal of Innovation Research and Knowledge, 2025)
This research uses a qualitative descriptive approach to analyze the phenomenon of hybrid language and textism in YouTube comments. Hybrid language in digital communications includes code-mixing and code-switching, but only code-mixing is found in YouTube comments. Of the various types of code-mixing, the most dominant form is word insertion, namely inserting words from another language into the main sentence. This shows that users prefer mixing languages in the form of single words because it is more concise and efficient in fast and informal digital interactions. Meanwhile, textism is a form of deviation from standard spelling or grammar that is often used to speed up digital communication. In the textism category, acronyms are the most dominant form, used to save time and adapt to digital language trends. These findings indicate that in communication on social media platforms such as YouTube, efficiency and ease in conveying messages are the main factors in choosing the form of language used.